Identifying Atypical Femoral Fractures—A Retrospective Review - Juby, Angela G.; Crowther, Sean; Cree, Marilyn (Calcified tissue international, 2014)
Subtrochanteric atypical femoral fractures (AFFs) have been reported in patients on osteoporosis therapy (bisphosphonates and denosumab). In 2010, and again in 2013, the ASBMR AFF Task Force developed strict diagnostic criteria for AFFs. This is the first study using these criteria to define the prevalence of AFFs in Canada. This study is a retrospective review of all adult patients (April 2002–March 2013) with an ICD 10 code for hip, femoral or subtrochanteric fracture, from two referral hospitals in Alberta, Canada. All identified as isolated subtrochanteric fractures were further evaluated by chart review, prescription review and examination of radiographs. Of 349 subjects, 79 had isolated subtrochanteric fractures. Of the 70 cases of subtrochanteric fractures that were radiographically assessed (9 films unavailable), 41 fulfilled ASBMR 2013 AFF criteria. The remaining subjects had subtrochanteric fractures but did not meet the ASBMR criteria to qualify as AFFs. There were 11 AFFs in 2012/2013, giving a rate of AFFs of 1.42 per 100,000 50 + year adults, compared to a rate of 103.47 per 100,000 50+ year adults for typical hip fractures. Isolated subtrochanteric fractures are rare. They cannot reliably be identified by ICD coding alone. In this study, only 59 % of all isolated subtrochanteric/femoral shaft fractures fulfilled the ASBMR task force criteria for true AFFs. The rate of typical hip fractures was substantially higher than the rate of AFFs, defined by ASBMR diagnostic criteria.